PENGARUH KESIAPAN BELAJAR DAN KECERDASAN EMOSIONAL TERHADAP HASIL BELAJAR : Survey Pada Mahasiswa Fakultas Pendidikan Ekonomi dan Bisnis Universitas Pendidikan Indonesia Angkatan 2018 - Dhea Maulidina Rahayu, - (2020)
The background of this research is the low learning outcomes of students the Faculty of Economics and Business Education in Indonesia Education University class of 2018 as seen from the cumulative achievement index. This research aims to determine the effect of learning readiness and emotional intelligence on student learning outcomes, the method of this research is explanatory survey. The population in this research was 651 students. By using a random sampling technique, a sample of 248 students was obtained. The technique of data analysis used multiple linear regression analysis. The findings of this research indicate the: (1) students' learning readiness is in the high category and there is a positive influence on learning readiness on the learning outcomes of students the Faculty of Economics and Business Education in Indonesian Education University class of 2018. (2) emotional intelligence is in the medium category and there is influence positive on emotional intelligence on the learning outcomes of students the Faculty of Economics and Business Education in Indonesian Education University class of 2018. Keywords: Learning Readiness, Emotional Intelligence, and Learning Outcomes.